COMMUNICATION AS CARE AT END OF LIFE: AN EMERGING ISSUE FROM AN EXPLORATORY ACTION RESEARCH STUDY OF RENAL END‐OF‐LIFE CARE FOR ETHNIC MINORITIES IN THE UK. Issue 1 (September 2014) - Wilkinson, Emma; Randhawa, Gurch; Brown, Edwina A.; Da Silva Gane, Maria; Stoves, John; Warwick, Graham; Akhtar, Tahira; Magee, Regina; Sharman, Sue; Farrington, Ken; Brown, Edwina A.; Farrington, Ken
SUMMARY South Asian people have a higher risk of developing kidney disease, are disproportionately represented in the patient population requiring renal replacement therapy and wait longer to receive a kidney transplant, compared with white Europeans. As a result, there is a demand for end‐of‐life care, which meets the needs of this group of patients. Providing end‐of‐life care to patients from different cultures is a challenge for renal services as there can be barriers to communication in the form of language, delegated decision‐making within families and reluctance to discuss death. To explore end‐of‐life care for South Asians with kidney disease, 16 interviews with patients and 14 focus groups with care providers were conducted at four research sites in the UK with large South Asian populations. Using an action research design the data were analysed thematically and fed back to inform the research in a cyclical manner. If patients are not fully aware of their condition or of what end‐of‐life care is, it is less likely that they will be able to be involved in decision‐making about their care and this is compounded where there are communication barriers. Variations in care provider awareness and experience of providing end‐of‐life care to South Asian patients, in turn, contributes to lack of patient awareness of end‐of‐life care. Communication as care at the end of life should be explored further. Researching the South Asian patient experience of end of life highlights many relevant and generalisable issues.